Early-onset ischaemic stroke: Analysis of 58 polymorphisms in 17 genes involved in methionine metabolism - Giusti, Betti; Saracini, Claudia; Bolli, Paola; Magi, Alberto; Martinelli, Ida; Peyvandi, Flora; Rasura, Maurizia; Volpe, Massimo; Lotta, Luca A.; Rubattu, Speranza; Mannucci, Pier Mannuccio; Abbate, Rosanna (Thrombosis and Haemostasis, 2010)
The hypothesis underlying this study is that variations in genes involved in methionine metabolism may contribute to genetic susceptibility for early-onset ischaemic stroke. We investigated 58 polymorphisms in AHCY, BHMT, BHMT2, CBS, ENOSF1, FOLH1, MTHFD1, MTHFR, MTR, MTRR, NNMT, PON1, PON2, SLC19A1, SHMT1, TCN2, TYMS genes on genomic DNA from 501 young patients who survived ischaemic stroke and 1,211 sex and age comparable controls. Genotype distribution was significantly different between patients and controls for the following SNPs: rs10037045 BHMT, rs682985 BHMT2, rs1051319 CBS, rs202680 FOLH1, rs2274976 MTHFR, rs1979277 SHMT1, rs20721958 TCN2. On multiple logistic regression analysis adjusted for traditional risk factors, rs10037045 BHMT, rs682985 BHMT2, rs1051319 CBS, and rs202680 FOLH1 remained independent risk factors for stroke. After haplotype reconstruction, generalised linear model analyses adjusted for traditional risk factors and using the FDR multiple testing correction showed significant associations between ischaemic stroke and BHMT, CBS, FOLH1, MTR, PON2, TCN2 and TYMS haplotypes. This study identifies significant genetic associations between premature ischaemic stroke and haplotypes in BHMT, CBS, FOLH1, MTR, PON2, TCN2 and TYMS genes involved in methionine metabolism.
Keywords: Ischaemic stroke; methionine metabolism; homocysteine; polymor-phism; haplotype